Direct Evidence of Abortive Lytic Infection-Mediated Establishment of Epstein-Barr Virus Latency During B-Cell Infection - Inagaki, Tomoki; Sato, Yoshitaka; Ito, Jumpei; Takaki, Mitsuaki; Okuno, Yusuke; Yaguchi, Masahiro; Masud, H. M. Abdullah Al; Watanabe, Takahiro; Sato, Kei; Iwami, Shingo; Murata, Takayuki; Kimura, Hiroshi (Frontiers in Microbiology, 2021)
Viral infection induces dynamic changes in transcriptional profiles. Virus-induced and anti-viral responses are intertwined during the infection. Epstein-Barr virus (EBV) is a human gammaherpesvirus that provides a model of herpesvirus latency. To measure the transcriptome changes during the establishment of EBV latency, we infected EBV-negative Akata cells with EBV-EGFP and performed by transcriptome sequencing (RNA-seq) at 0, 2, 4, 7, 10, and 14 days after infection. We found transient downregulation of mitotic division-related genes, reflecting reprogramming of cell growth by EBV, and a burst of viral lytic gene expression in the early phase of infection. Experimental and mathematical investigations demonstrated that infectious virions were not produced in the pre-latent phase, suggesting the presence of an abortive lytic infection. Fate mapping using recombinant EBV provided direct evidence that the abortive lytic infection in the pre-latent phase converges to latent infection during EBV infection of B-cells, shedding light on novel roles of viral lytic gene(s) in establishing latency. Furthermore, we found that the BZLF1 protein which is a key regulator of reactivation was dispensable for abortive lytic infection in the pre-latent phase, suggesting the divergent regulation of viral gene expressions from a productive lytic infection.